PENERAPAN MODEL PEMBELAJARAN LBD UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SMAN 1 BUNGO - wiji, wiji (Jurnal Tunas Pendidikan, 2022)
This research is a class action research / CAR (Classroom Action Research) which aims to improve the activities and learning outcomes of students in class XI MIPA SMA N 1 Bungo through the application of the LBD learning model. This research was conducted at SMAN 1 Bungo, with the subjects being students of class XI MIPA 4 in the even semester of the 2019/2020 school year. The data in the study were obtained based on the results of questionnaires, interviews, learning observations and final learning outcomes. From the results of the student activity observation sheet, the percentage of student participation increased from the first cycle of 69.98% to 79.37% in the second cycle and has met the indicator of student participation, namely 75%. Based on the average value of learning outcomes obtained by students in the first cycle of 68.09, it increased to 74.81 in the second cycle and the percentage of classical completeness from 12.12% increased to 87.88% and this met the indicators of success, namely classical mastery reaching 85% with a KKM of 75. So it can be concluded that learning chemistry using the Laboratory Based Discovery (LBD) learning model can increase the activity and learning outcomes of students' chemistry on the colloid system concept.